2011
DOI: 10.1080/19376529.2011.615774
|View full text |Cite
|
Sign up to set email alerts
|

Taking Message-Attitude Congruence as Media Effects: Examining Perceived Influence of Political Talk Radio in Hong Kong

Abstract: This study examines how people perceive the influence of political talk radio in Hong Kong. Theoretically, the study focuses on the influence of messageattitude congruence, that is, the situation in which a person's opinions or attitudes are consistent with the viewpoints promulgated by media messages, on the third-person perception. It is argued that message-attitude congruence provides a situation in which people may attribute their attitudes partly to media influence. Hence message-attitude congruence is ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Participants who liked DTC advertisements exhibited less TPP (Taylor, Bell & Kravitz, 2011). A study of adults in Hong Kong found that TPP regarding political talk radio was predicted by message/ attitude congruence: If you agree with and/or like a message, TPP diminishes (Lee, 2011).…”
Section: Tpp and Attitudesmentioning
confidence: 99%
“…Participants who liked DTC advertisements exhibited less TPP (Taylor, Bell & Kravitz, 2011). A study of adults in Hong Kong found that TPP regarding political talk radio was predicted by message/ attitude congruence: If you agree with and/or like a message, TPP diminishes (Lee, 2011).…”
Section: Tpp and Attitudesmentioning
confidence: 99%